2019
DOI: 10.1111/jbi.13691
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy patterns and upper range limits of lowland Bornean birds along an elevational gradient

Abstract: Aim The traditional view of species’ distributions is that they are less abundant near the edges of their ranges and more abundant towards the centre. Testing this pattern is difficult because of the complexity of distributions across wide geographical areas. An alternative strategy, however, is to measure species’ distributional patterns along elevational gradients. We applied this strategy to examine whether lowland forest birds are indeed less common near their upper range limits on a Bornean mountain, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…We found that bird species distributions can differ significantly and consistently among mountains, and that both abiotic factors and species interactions contribute to these differences. This knowledge is important as we construct models to predict elevational range shifts under future climate change scenarios (Burner, Styring, Rahman, & Sheldon, ). Most future projections have been based solely on temperature (Chen et al, ; Forero‐Medina et al, ; Grytnes, Beaman, Romdal, & Rahbek, ), or temperature plus precipitation (Tingley, Monahan, Beissinger, & Moritz, ), but evidence now suggests that reactions of natural communities to climate change have more complex underpinnings (Devictor et al, ; Dulle et al, ; Tingley et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that bird species distributions can differ significantly and consistently among mountains, and that both abiotic factors and species interactions contribute to these differences. This knowledge is important as we construct models to predict elevational range shifts under future climate change scenarios (Burner, Styring, Rahman, & Sheldon, ). Most future projections have been based solely on temperature (Chen et al, ; Forero‐Medina et al, ; Grytnes, Beaman, Romdal, & Rahbek, ), or temperature plus precipitation (Tingley, Monahan, Beissinger, & Moritz, ), but evidence now suggests that reactions of natural communities to climate change have more complex underpinnings (Devictor et al, ; Dulle et al, ; Tingley et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Freeman and Beehler (2018) found that only one‐third of avian species showed a unimodal symmetric abundance distribution along a New Guinean elevational gradient. A similar proportion (30%) of species displayed such spatial patterns on a Bornean mountain (Burner et al., 2019). These previous findings together with our research demonstrate that species may show heterogeneous abundance patterns along an elevational gradient.…”
Section: Discussionmentioning
confidence: 76%
“…Our study of species' elevational abundance patterns, including evidence from five commonly distributed and abundant small mammal species along 12 elevational gradients, provides a rigorous assessment of the ACH along the elevational centre‐periphery axis, which is largely underrepresented in the ACH literature (Burner et al., 2019). We found very limited evidence supporting the consistent relationship between species abundance distributions and the ACH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations